PERAN KEPALA MADRASAH DALAM MENINGKATKAN KINERJA TENAGA KEPENDIDIKAN DI MTSN 4 TABALONG - Chairul Echwan (ADIBA : JOURNAL OF EDUCATION, 2023)
This research is motivated by the problem that the Madrasah Head has a very important role in driving madrasah management so that it can run according to the various demands of society and the times. Therefore, the role of a successful madrasah head can be seen from the achievement of madrasah objectives, as well as the increased performance of educational staff within the madrasah environment. The purpose of this research is to find out the role of the madrasah head as a leader and as a manager in improving the performance of educational staff and what are the supporting and inhibiting factors faced by madrasah head in improving the performance of education staff. The type and approach used in this research is by way of field research with a qualitative descriptive approach. The object of this research is the role of the madrasa head as a leader and as a manager in improving the performance of teaching staff at MTsN 4 Tabalong and the research subjects are the head of MTsN 4 Tabalong, the deputy head of the curriculum section, the head of administration, the head of the library, and the security guard. Furthermore, the collection technique uses observation, structured interviews, and documentation. Then the data analysis in this study was carried out in three stages including data reduction, data presentation and conclusion/verification. The results showed that the role of the madrasa head as a leader in improving the performance of teaching staff at MTsN 4 Tabalong was by fostering discipline in the form of direction and supervision, providing motivation in the form of words of encouragement, rewards in the form of certificates, and perceptions in the form of facilitation. Meanwhile, the role of the madrasa head as a manager in improving the performance of teaching staff at MTsN 4 Tabalong is by empowering teaching staff through cooperation and coordination, providing opportunities for teaching staff to improve their profession with training, and encouraging the involvement of all educational staff in all madrasah activities by directing them to involved. The supporting factors carried out by the madrasa head in improving the performance of teaching staff at MTsN 4 Tabalong are responsibility for assignments, respect for assignments, and the work environment, and the inhibiting factors are time, social jealousy and opportunities for development.